Nanosilver / graphene / polymer composite emulsion and preparation method and application thereof
By loading nanosilver on graphene and dispersing it in a polymer emulsion to form a composite emulsion, the problem of insufficient protective film performance in the prior art is solved, and better wear resistance, stain resistance, antibacteriality and antistatic properties are achieved.
Patent Information
- Application Number
- CN202410884880.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-02
AI Technical Summary
When designing curved screens and folded screen protective films, it is difficult for the prior art to meet the requirements of bending resistance, wear resistance, stain resistance, antistatic and antibacterial properties at the same time.
By loading nanosilver on graphene and dispersing it evenly in a polyurethane-acrylate polymer emulsion with a core-shell structure, a stable nanosilver/graphene/polymer composite emulsion is formed as a coating for the folding screen protective film.
It significantly improves the antibacterial, antistatic and wear resistance of the composite emulsion, and improves stain resistance and bending resistance, and is suitable for folding screen protective film for electronic equipment.
Smart Images

Figure BDA0004926695480000191 
Figure BDA0004926695480000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and more specifically to a nano silver / graphene / polymer composite emulsion and a preparation method and application thereof. Background Art
[0002] With the continuous development and update of science and technology, curved screen and folding screen technology have become two highlights of electronic devices, especially leading a trend of innovation in the field of smart phones and tablets. Compared with traditional straight screen electronic devices, the design and manufacture of protective films for curved screen and folding screen electronic devices have higher requirements in terms of dynamic fit, flexibility and tolerance.
[0003] In addition, generally speaking, the protective film of electronic equipment needs to be coated on the surface of the substrate, and the coating not only gives the protective film certain scratch resistance, wear resistance, stain resistance and other properties, but also affects the flexibility of the protective film. In addition, as people's health awareness continues to improve, people are paying more and more attention to the antibacterial and anti-blue light properties of protective films, so the protective film coating is crucial.
[0004] The Chinese patent with publication number CN114163858A discloses a photocurable PET coating and a preparation method thereof, a preparation method of a PET substrate and its application, wherein the photocurable PET coating comprises the following components in parts by weight: 35-45 parts of polyurethane; 50-65 parts of polymethacrylate; 1-5 parts of nano-silicon dioxide; 10-20 parts of active monomers; 2-6 parts of photoinitiators; 0.1-1 parts of leveling agents. The photocurable PET coating obtained by this technical solution has a low resilience, strong scratch resistance, and high hardness after curing, and can be applied to curved screens. However, the low resilience of this technical solution may cause marks on the folding screen, affecting the appearance.
[0005] The Chinese patent with publication number CN115873461A discloses a bending-resistant coating and a bending-resistant film. The bending-resistant coating includes the following raw material components by weight: 40-80 parts of acrylic resin; 5-30 parts of modified nanoparticles; 0.01-1 parts of leveling agent; 1-6 parts of photoinitiator; 50-100 parts of diluent. This technical solution is to improve the bending resistance of the coating by adding modified nanoparticles, and it has good light transmittance and high reflectivity, and is suitable for application fields such as curved display screens, flexible display screens, and folding display screens. However, there is an upper limit to the bending resistance provided by the nanoparticles in this technical solution, and excessive addition will affect the haze of the protective film. Summary of the invention
[0006] The purpose of the present invention is to provide a nanosilver / graphene / polymer composite emulsion and a preparation method and application thereof. Nanosilver can be uniformly loaded on graphene, and the graphene-loaded nanosilver can be uniformly dispersed in the polymer emulsion to form a stable composite emulsion. When the obtained composite emulsion is used as a coating for a protective film of a folding screen of an electronic device, the problems of insufficient bending resistance, wear resistance, stain resistance, antistatic and antibacterial properties of the protective film are solved.
[0007] The first aspect of the present invention provides a nanosilver / graphene / polymer composite emulsion, wherein the raw materials include, by weight: 2-8 parts of graphene-loaded nanosilver and 80-100 parts of polymer emulsion; the polymer emulsion is a polyurethane-acrylate polymer emulsion with a core-shell structure;
[0008] The method for preparing graphene comprises the following steps:
[0009] S1, adding graphene to deionized water for ultrasonic mixing to obtain a graphene aqueous solution;
[0010] S2, adding aminopolyethylene glycol to the graphene aqueous solution, reacting at 80-90° C. for 18-24 hours, filtering, washing with ethanol, and drying to obtain;
[0011] The graphene is a compound of graphene oxide, porous graphene and nitrogen-doped graphene; the mass ratio is (10-20): (3-5): (0.5-1);
[0012] The graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm;
[0013] The pore size of the porous graphene is 3-5 nm;
[0014] The nitrogen-doped graphene has a nitrogen content of 1-2 at% and a diameter of 0.5-10 μm;
[0015] The amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, and the mass ratio is (1-3):1.
[0016] The inventors found that by grafting functional groups on the surface of graphene, the uniformity of nanosilver loading on the surface of graphene can be effectively improved through the anchoring effect of the functional groups. It was unexpectedly discovered that when the graphene is a composite of graphene oxide, porous graphene and nitrogen-doped graphene; and the mass ratio is (10-20):(3-5):(0.5-1), not only can the stability of graphene-loaded nanosilver in a polymer emulsion be improved, but also the obtained composite emulsion has more excellent wear resistance when used as a coating for a protective film of a folding screen of an electronic device. The inventors speculate that it is because the compounded graphene has different structures, thus obtaining diverse nanosilver loading forms, and the graphene-loaded nanosilver can provide more dispersion points and support points, so that it can exist stably in the polymer; at the same time, the diverse nanosilver loading forms make it possible to form a composite support structure between the graphene-loaded nanosilver, thereby effectively resisting external scratches and friction, and improving wear resistance; it is further found that the best effect is achieved when the graphene oxide is controlled to be a single-layer graphene oxide with a sheet diameter of 0.5-5μm and a thickness of 0.8-1.2nm.
[0017] Preferably, the mass ratio of the graphene, deionized water and amino polyethylene glycol is (0.2-1):100:(2-4), preferably 0.5:100:2.5.
[0018] Preferably, the graphene is a compound of graphene oxide, porous graphene and nitrogen-doped graphene; the mass ratio is 15:4:0.6.
[0019] Preferably, the amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, with a mass ratio of 2:1.
[0020] Preferably, the weight average molecular weight of the four-arm polyethylene glycol amino group is 8000-12000, preferably 10000.
[0021] Preferably, the weight average molecular weight of the aminopolyethylene glycol carboxyl group is 3000-7000, preferably 5000.
[0022] The invention utilizes the ring-opening reaction between amino polyethylene glycol and graphene to graft the amino polyethylene glycol on the surface of the graphene, and the nano silver can improve the loading efficiency and has good uniform dispersion when loading. Meanwhile, the inventors find that when the amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, the mass ratio is (1-3):1, and the weight average molecular weight of the four-arm polyethylene glycol amino group is controlled to be 8000-12000, and the weight average molecular weight of the amino polyethylene glycol carboxyl group is controlled to be 3000-7000, the dispersibility of the graphene-loaded nano silver in the polymer emulsion can be further improved, and the stain resistance of the composite emulsion can be improved. The inventors speculate that the graphene-loaded nanosilver modified by aminopolyethylene glycol under this condition can not only utilize the polyethylene glycol chain to improve the compatibility with the polymer emulsion, but also the obtained graphene-loaded nanosilver has more dispersion points and interaction points, making it more evenly dispersed in the polymer emulsion. In addition, the wettability of the surface of the graphene-loaded nanosilver is improved, so that the composite emulsion forms a more uniform coating on the surface of the folding screen protective film of the electronic device, while also making it more difficult for pollutants to adhere to its surface.
[0023] Preferably, the graphene-loaded nanosilver includes a first graphene-loaded nanosilver and a second graphene-loaded nanosilver; the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is (20-30):(0.5-1.5), preferably 25:1.
[0024] Preferably, the preparation method of the first graphene-loaded nanosilver is as follows: first, 0.15 g of graphene is dispersed in 100 mL of deionized water and ultrasonicated for 1-2 h, then 25 mL of 50 mmol / L silver nitrate solution is added and ultrasonicated at 30-40 ° C for 20-30 min; then 0.02 g of NaBH 4 , react at 25-30°C for 10-12h, add 0.5 mol / L sodium hydroxide aqueous solution to adjust the pH of the system to 11, centrifuge after the reaction, wash repeatedly with deionized water and ethanol, and dry to obtain.
[0025] Preferably, the preparation method of the second graphene-loaded nanosilver is as follows: first, 0.15 g of graphene is dispersed in 100 mL of deionized water and ultrasonicated for 1-2 h, then 25 mL of 50 mmol / L silver nitrate solution is added, and ultrasonicated at 30-40 ° C for 20-30 min; then 0.4 g of sodium citrate and 3 g of PVP are added, mixed evenly, 30 mL of hydrogen peroxide with a mass concentration of 20% is added, stirred for 1-3 min, and then 0.2 g of NaBH is added. 4 After reacting for 40-60 minutes, filter, wash and dry to obtain the product.
[0026] The inventors found in the experimental process that when the graphene-loaded nanosilver includes the first graphene-loaded nanosilver and the second graphene-loaded nanosilver; the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is (20-30): (0.5-1.5), the antibacterial and antistatic properties of the composite emulsion can be significantly improved while the wear resistance of the composite emulsion can be improved to a certain extent. The inventors speculate that it is because the nanosilver in the first graphene-loaded nanosilver and the second graphene-loaded nanosilver has different shapes, thereby increasing the surface area of the composite emulsion in contact with bacteria and increasing the probability of interaction with bacteria. At the same time, the compounded graphene-loaded nanosilver increases the microstructure of the coating surface, which is more conducive to the dispersion of static charges and the possibility of reducing static electricity accumulation; in addition, the compounded graphene-loaded nanosilver may change the elastic system of the composite emulsion, making it have better wear resistance.
[0027] Preferably, the method for preparing the polyurethane-acrylate polymer emulsion having a core-shell structure comprises the following steps:
[0028] S1. Preparation of polyurethane emulsion: under nitrogen protection, react pretreated castor oil, isocyanate and dibutyltin dilaurate at 70-90°C for 30-60min, add polyol and chain extender, and keep warm for 30-60min; cool to 60°C, add triethylamine for neutralization for 30-45min; cool to 20°C, add deionized water, and stir at 1000-3000r / min for 30-60min to obtain;
[0029] S2. Preparation of core layer polyurethane grafted acrylic polymer: stir the first acrylate monomer, emulsifier, deionized water and polyurethane emulsion evenly, add ammonium persulfate at 60-70° C., and keep warm for 30-60 minutes to obtain;
[0030] S3. Preparation of core-shell polyurethane-acrylate composite emulsion:
[0031] Slowly add the second acrylate monomer and ammonium persulfate to the core layer polyurethane grafted acrylic polymer, react at 70-80° C. for 1-2 hours, and after the reaction is completed, add ammonia water dropwise to adjust the pH to 7-8 to obtain the product.
[0032] Preferably, the method for preparing the pretreated castor oil is: dehydrating the castor oil at 70-80° C. for 1-3 h.
[0033] Preferably, the acid value of the castor oil is ≤1.80 mgKOH / g, preferably 1.60 mgKOH / g.
[0034] Preferably, the isocyanate is selected from at least one of isophorone diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate and decamethylene diisocyanate, preferably isophorone diisocyanate.
[0035] Preferably, the polyol is at least one selected from polyethylene adipate, polyethylene adipate acetal, polybutylene adipate-1,4-diol, polyethylene terephthalate, and polyneopentyl adipate.
[0036] Preferably, the polyol is a compound of polyethylene adipate and poly(1,4-butylene adipate) in a mass ratio of (1-3):1, preferably 2.5:1.
[0037] Preferably, the weight average molecular weight of the polyethylene adipate is 600-2000, and the hydroxyl value is 56±3 mgKOH / g. Preferably, the weight average molecular weight is 1000, and the hydroxyl value is 56±3 mgKOH / g.
[0038] Preferably, the weight average molecular weight of the poly(1,4-butylene adipate) is 3000-
[0039] 5000, and the hydroxyl value is 28±2 mgKOH / g. Preferably, the weight average molecular weight is 4000, and the hydroxyl value is 28±2 mgKOH / g.
[0040] Preferably, the chain extender is selected from at least one of dimethylol propionic acid, dimethylol butyric acid, neopentyl glycol, 1,4-butanediol, polyethylene glycol, 1,6-hexanediol, and diethylene glycol.
[0041] Preferably, the chain extender is a compound of dimethylolpropionic acid, neopentyl glycol and 1,6-hexanediol in a mass ratio of (4-8):(1-3):(1-3), preferably 6:1:2.
[0042] Preferably, the mass ratio of castor oil to polyol is (1.1-1.5):1, preferably 1.3:1.
[0043] Preferably, the amount of isocyanate added is n(NCO / OH)=1.1-1.3.
[0044] Preferably, the mass ratio of the chain extender to the polyol is (1-2):(10-15), preferably 1.5:12.
[0045] Preferably, based on the total weight of the polyurethane emulsion, the added amount of dibutyltin dilaurate is 20-100 ppm, preferably 50 ppm.
[0046] Preferably, based on the total weight of the polyurethane emulsion, the amount of triethylamine added is 20-100 ppm, preferably 80 ppm.
[0047] Preferably, based on the total weight of the polyurethane emulsion, the amount of deionized water added is 70-85%, preferably 80%.
[0048] Preferably, the first acrylic acid ester monomer is at least one selected from butyl acrylate, ethyl acrylate, isobutyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate.
[0049] Preferably, the first acrylic acid ester monomer is a compound of butyl acrylate, hydroxyethyl acrylate and hydroxypropyl acrylate in a mass ratio of 1:(1-3):(2-4), preferably 1:2:3.
[0050] Preferably, the second acrylate monomer is at least one selected from butyl acrylate, methyl acrylate, methyl methacrylate, acrylic acid, and ethyl acrylate.
[0051] Preferably, the second acrylate monomer is a compound of methyl methacrylate, acrylic acid and ethyl acrylate in a mass ratio of (0.5-2):(4-6):(3-5), preferably 1:5:4.
[0052] Preferably, the emulsifier is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and octylphenol polyglycol ether.
[0053] Preferably, the mass ratio of the first acrylate monomer, emulsifier, deionized water, polyurethane emulsion and ammonium persulfate in S2 is (8-15): (1-2): (15-20):
[0054] (1-5):(0.1-0.5), preferably 12:1.5:18:3:0.3.
[0055] Preferably, the mass ratio of the core layer polyurethane grafted acrylic polymer, the second acrylate monomer, and ammonium persulfate in S3 is (10-20):(8-15):(0.05-0.2), preferably 15:10:0.1.
[0056] Based on the composite emulsion of the present invention as a protective film coating for the folding screen of an electronic device, the coating is required to have excellent bending resistance. Although the present invention uses a specific graphene to uniformly load nanosilver in graphene, the obtained graphene-loaded nanosilver can be stably present in a polymer emulsion, and the obtained composite emulsion has good wear resistance, antifouling, antibacterial, and antistatic properties, but due to the presence of nanosilver, when the composite emulsion coating is subjected to external force, there will be a certain stress concentration, resulting in general bending resistance of the coating. To solve this problem, the inventors synthesized a polymer emulsion with a specific core-shell structure by using a specific polyurethane emulsion, a specific first acrylate monomer, and a specific second acrylate monomer, which can effectively withstand external stress, reduce the influence of external stress on the coating, and maintain deformation ability when bending while the coating has a certain stain resistance. The inventors speculate that this is because the composite emulsion formed by the core-shell polyurethane-acrylate composite emulsion prepared by the present invention and the graphene-loaded nanosilver can not only form a more uniform and smoother surface, reducing the attachment points of pollutant particles, but also can avoid leaving pollutants while forming a protective film to reduce the attachment of pollutants.
[0057] The second aspect of the present invention provides a method for preparing a nanosilver / graphene / polymer composite emulsion, comprising the following steps: ultrasonically mixing the graphene-loaded nanosilver and the polymer emulsion for 20-40 minutes to obtain the composite emulsion.
[0058] The third aspect of the present invention provides the application of the above-mentioned nanosilver / graphene / polymer composite emulsion as a coating for a protective film of a folding screen of an electronic device.
[0059] Beneficial effects:
[0060] 1. The inventors grafted functional groups on the surface of graphene, and the uniformity of the loading of nanosilver on the surface of graphene can be effectively improved through the anchoring effect of the functional groups. When the graphene is a composite of graphene oxide, porous graphene and nitrogen-doped graphene; and the mass ratio is (10-20): (3-5): (0.5-1), not only the stability of the graphene-loaded nanosilver in the polymer emulsion can be improved, but also the obtained composite emulsion has better wear resistance when used as a protective film coating for folding electronic devices.
[0061] 2. The present invention utilizes the ring-opening reaction between amino polyethylene glycol and graphene to graft amino polyethylene glycol on the surface of graphene. When nanosilver is loaded, the loading efficiency can be improved and the nanosilver has good uniform dispersion. When the amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, the mass ratio is (1-3): 1, and the weight average molecular weight of the four-arm polyethylene glycol amino group is controlled to be 8000-12000, and the weight average molecular weight of the amino polyethylene glycol carboxyl group is controlled to be 3000-7000, the dispersibility of the graphene-loaded nanosilver in the polymer emulsion can be further improved while improving the stain resistance of the composite emulsion.
[0062] 3. In the present invention, when the graphene-loaded nanosilver includes a first graphene-loaded nanosilver and a second graphene-loaded nanosilver; and the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is (20-30): (0.5-1.5), the antibacterial and antistatic properties of the composite emulsion can be significantly improved while also improving the wear resistance of the composite emulsion to a certain extent.
[0063] 4. The present invention adopts a specific polyurethane emulsion, a specific first acrylate monomer, and a specific second acrylate monomer to synthesize a polymer emulsion with a specific core-shell structure, which can effectively withstand external stress and reduce the influence of external stress on the coating film. The coating film has a certain stain resistance while maintaining deformation ability when bent. DETAILED DESCRIPTION
[0064] In order to better explain the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the examples in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other implementation methods obtained by those skilled in the art without making creative work are within the scope of protection of the present invention. The experimental methods in the following embodiments, unless otherwise specified, are conventional methods, and the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial channels.
[0065] Example 1
[0066] Example 1 provides a nanosilver / graphene / polymer composite emulsion, wherein the raw materials include, by weight: 5 parts of graphene-loaded nanosilver and 90 parts of polymer emulsion; the polymer emulsion is a polyurethane-acrylate polymer emulsion with a core-shell structure.
[0067] The method for preparing graphene comprises the following steps:
[0068] S1, adding graphene to deionized water for ultrasonic mixing to obtain a graphene aqueous solution;
[0069] S2. Add aminopolyethylene glycol to the graphene aqueous solution, react at 85° C. for 20 h, filter, wash with ethanol, and dry to obtain the product.
[0070] The graphene is a compound of graphene oxide, porous graphene and nitrogen-doped graphene; the mass ratio is 15:4:0.6.
[0071] The graphene oxide is a single-layer graphene oxide with a sheet diameter of 2.75±2.25 μm and a thickness of 1.0±0.2 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number 100394.
[0072] The porous graphene has a pore size of 4.58 nm and was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with a product number of 103157.
[0073] The nitrogen-doped graphene has a nitrogen content of 1.2 at% and a diameter of 5.25±4.75 μm, and was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number 104021.
[0074] The mass ratio of the graphene, deionized water and amino polyethylene glycol is 0.5:100:2.5.
[0075] The amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, with a mass ratio of 2:1.
[0076] The four-arm polyethylene glycol amino group has a weight average molecular weight of 10,000 and was purchased from Shanghai Pengshuo Biotechnology Co., Ltd. with the product number PS4-N-10K.
[0077] The amino polyethylene glycol carboxyl group has a weight average molecular weight of 5000 and was purchased from Shanghai Pengshuo Biotechnology Co., Ltd. with the product number PS2-NCM-5k.
[0078] The graphene-loaded nanosilver comprises a first graphene-loaded nanosilver and a second graphene-loaded nanosilver; the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is 25:1.
[0079] The preparation method of the first graphene-loaded nanosilver is as follows: first, 0.15 g of graphene is dispersed in 100 mL of deionized water and ultrasonicated for 1.5 h, then 25 mL of 50 mmol / L silver nitrate solution is added and ultrasonicated at 35° C. for 25 min; then 0.02 g of NaBH 4 , react at 30°C for 12 hours, add 0.5 mol / L sodium hydroxide aqueous solution to adjust the pH of the system to 11, centrifuge after the reaction, wash repeatedly with deionized water and ethanol, and dry to obtain.
[0080] The preparation method of the second graphene-loaded nanosilver is as follows: first, 0.15 g of graphene is dispersed in 100 mL of deionized water and ultrasonicated for 1.5 h, then 25 mL of 50 mmol / L silver nitrate solution is added, and ultrasonic treatment is performed at 35° C. for 25 min; then, 0.4 g of sodium citrate and 3 g of PVP are added, mixed evenly, 30 mL of hydrogen peroxide with a mass concentration of 20% is added, stirred for 2 min, and then 0.2 g of NaBH is added. 4 After reacting for 50 min, filter, wash and dry.
[0081] The method for preparing the polyurethane-acrylate polymer emulsion with a core-shell structure comprises the following steps:
[0082] S1. Preparation of polyurethane emulsion: under nitrogen protection, pretreated castor oil, isocyanate and dibutyltin dilaurate were reacted at 80°C for 45 minutes, polyol and chain extender were added, and the reaction was kept warm for 50 minutes; the temperature was lowered to 60°C, and triethylamine was added for neutralization for 40 minutes;
[0083] Cool down to 20℃, add deionized water, and stir at 2000r / min for 45min.
[0084] S2. Preparation of core layer polyurethane grafted acrylic polymer: stir the first acrylate monomer, emulsifier, deionized water and polyurethane emulsion evenly, add ammonium persulfate at 65° C., and keep warm for 50 minutes to obtain;
[0085] S3. Preparation of core-shell polyurethane-acrylate composite emulsion:
[0086] Slowly add the second acrylate monomer and ammonium persulfate to the core layer polyurethane grafted acrylic polymer, react at 75° C. for 1.5 hours, and after the reaction is completed, add ammonia water dropwise to adjust the pH to 8 to obtain the product.
[0087] The method for preparing the pretreated castor oil is as follows: dehydrating the castor oil at 75° C. for 2 hours.
[0088] The castor oil has an acid value of 1.60 mgKOH / g and is purchased from Inner Mongolia Weiyu Biotechnology Co., Ltd. Model: NO.1 castor oil premium grade.
[0089] The isocyanate is isophorone diisocyanate.
[0090] The polyol is a compound of polyethylene adipate and polybutylene adipate-1,4-diol, with a mass ratio of 2.5:1.
[0091] The polyethylene adipate has a weight average molecular weight of 1000 and a hydroxyl value of 56±3 mgKOH / g, and is purchased from Xuzhou Yihuiyang New Materials Co., Ltd., model: HY-2020.
[0092] The poly(1,4-butylene adipate) has a weight average molecular weight of 4000 and a hydroxyl value of 28±2 mgKOH / g. It was purchased from Shandong Baiqian Chemical Co., Ltd., model: HY-4022.
[0093] The chain extender is a compound of dimethylol propionic acid, neopentyl glycol and 1,6-hexanediol in a mass ratio of 6:1:2.
[0094] The mass ratio of the castor oil to the polyol is 1.3:1.
[0095] The mass ratio of the chain extender to the polyol is 1.5:12.
[0096] The amount of isocyanate added is n(NCO / OH)=1.2.
[0097] Based on the total weight of the polyurethane emulsion, the added amount of the dibutyltin dilaurate is 50 ppm.
[0098] Based on the total weight of the polyurethane emulsion, the added amount of the triethylamine is 80 ppm.
[0099] Based on the total weight of the polyurethane emulsion, the added amount of the deionized water is 80%.
[0100] The first acrylate monomer is a compound of butyl acrylate, hydroxyethyl acrylate and hydroxypropyl acrylate in a mass ratio of 1:2:3.
[0101] The second acrylate monomer is a compound of methyl methacrylate, acrylic acid and ethyl acrylate in a mass ratio of 1:5:4.
[0102] The emulsifier is sodium dodecylbenzene sulfonate.
[0103] The mass ratio of the first acrylate monomer, emulsifier, deionized water, polyurethane emulsion and ammonium persulfate in S2 is 12:1.5:18:3:0.3.
[0104] The mass ratio of the core layer polyurethane grafted acrylic polymer, the second acrylate monomer, and ammonium persulfate in S3 is 15:10:0.1.
[0105] A method for preparing a nanosilver / graphene / polymer composite emulsion comprises the following steps: ultrasonically mixing graphene-loaded nanosilver and polymer emulsion for 30 minutes to obtain the composite emulsion.
[0106] An application of a nanosilver / graphene / polymer composite emulsion is used as a protective film coating for a folding screen of an electronic device.
[0107] Example 2
[0108] Example 2 provides a nanosilver / graphene / polymer composite emulsion, and the specific implementation manner is the same as that of Example 1, except that, by weight, the raw materials include: 3 parts of graphene-loaded nanosilver and 80 parts of polymer emulsion.
[0109] Example 3
[0110] Example 3 provides a nanosilver / graphene / polymer composite emulsion, and the specific implementation manner is the same as that of Example 1, except that, by weight, the raw materials include: 7 parts of graphene-loaded nanosilver and 100 parts of polymer emulsion.
[0111] Comparative Example 1
[0112] Comparative Example 1 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. The specific implementation manner is the same as that of Example 1, except that the graphene is a composite of graphene oxide and porous graphene in a mass ratio of 15:4.
[0113] Comparative Example 2
[0114] Comparative Example 2 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. The specific implementation manner is the same as that of Example 1, except that the graphene is a compound of graphene oxide, porous graphene and nitrogen-doped graphene in a mass ratio of 25:2:2.
[0115] Comparative Example 3
[0116] Comparative Example 3 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application. Its specific implementation method is the same as Example 1, except that the single-layer graphene oxide is replaced by a multi-layer graphene oxide with 3.5±1.5 layers, a diameter of 5.5±1.5, and a thickness of 2±1 nm, which is purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0117] Comparative Example 4
[0118] Comparative Example 4 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. The specific implementation manner is the same as that of Example 1, except that the aminopolyethylene glycol is a compound of four-arm polyethylene glycol amino and aminopolyethylene glycol carboxyl, with a mass ratio of 0.5:1.
[0119] Comparative Example 5
[0120] Comparative Example 5 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. Its specific implementation manner is the same as that of Example 1, except that the four-arm polyethylene glycol amino group is replaced by a six-arm polyethylene glycol amino group. The weight average molecular weight of the six-arm polyethylene glycol is 10,000, and it is purchased from Shanghai Pengshuo Biotechnology Co., Ltd., item number: PS6-N-10K.
[0121] Comparative Example 6
[0122] Comparative Example 6 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. The specific implementation manner is the same as that of Example 1, except that the weight average molecular weight of the aminopolyethylene glycol carboxyl group is 10,000, which is purchased from Shanghai Pengshuo Biotechnology Co., Ltd., item number: PS2-NCM-10K.
[0123] Comparative Example 7
[0124] Comparative Example 7 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. The specific implementation manner is the same as that of Example 1, except that the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is 15:2.
[0125] Comparative Example 8
[0126] Comparative Example 8 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof, and its specific implementation manner is the same as that of Example 1, except that the graphene-loaded nanosilver includes a first graphene-loaded nanosilver.
[0127] Comparative Example 9
[0128] Comparative Example 9 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. Its specific implementation manner is the same as that of Example 1, except that poly(1,4-butylene adipate) is replaced with poly(neopentyl adipate) having a weight average molecular weight of 2000 and a hydroxyl value of 56±3 mgKOH / g. It is purchased from Xuzhou Yihuiyang New Materials Co., Ltd., model: XCP-2000N.
[0129] Comparative Example 10
[0130] Comparative Example 10 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. Its specific implementation manner is the same as that of Example 1, except that the first acrylate monomer is a compound of butyl acrylate, isooctyl acrylate and hydroxybutyl acrylate in a mass ratio of 1:4:1.
[0131] Comparative Example 11
[0132] Comparative Example 11 provides a nanosilver / graphene / polymer composite emulsion, a preparation method and an application thereof. Its specific implementation manner is the same as that of Example 1, except that the second acrylate monomer is a compound of butyl acrylate, methyl acrylate and methyl methacrylate in a mass ratio of 1:5:4.
[0133] Performance Test:
[0134] 1. The nanosilver / graphene / polymer composite emulsions prepared in Examples 1-3 and Comparative Examples 1-11 were left to stand at 25° C. for 6 months to observe whether sedimentation occurred.
[0135] 2. The nanosilver / graphene / polymer composite emulsion prepared in Examples 1-3 and Comparative Examples 1-11 was coated on a PET film with a thickness of 50 μm and a coating thickness of 1.5
[0136] μm, and the protective film was obtained after baking at 90℃ for 60s. The protective film was tested as follows:
[0137] Transmittance / haze: Refer to standard GB / T 2410-2008 "Test method for light transmittance and haze of transparent plastics".
[0138] Bending resistance: Use a flexible OLED bending tester to bend the coating outward at an angle of 180° for 100,000 times, and observe whether there are cracks or cracks on the surface of the coating.
[0139] Antibacterial property: Tested with reference to GB / T21866-2008, with Escherichia coli and a bacterial concentration of 5.8×10 5 CFU / ML, Staphylococcus aureus, bacterial concentration is 6.1×10 5 CFU / ML, the bactericidal rate was determined after 24 hours of contact.
[0140] Wear resistance: Use steel wool test machine at 500g / cm 2 Under a load of 1 kg, use #0000 steel wool to rub back and forth on the coating surface to check whether the coating is scratched.
[0141] Stain resistance: Use a contact angle meter to measure the water contact angle of the coating. The larger the contact angle, the better the stain resistance.
[0142] Antistatic property: Use a high resistance meter to measure the surface resistance of the coating.
[0143] The test results are shown in Tables 1 and 2.
[0144] Test results:
[0145] Table 1: Test results
[0146]
[0147] Table 2: Test results
[0148]
[0149] It can be seen from Table 1 and Table 2 that the stability and wear resistance of the composite emulsion obtained in Comparative Examples 1-3 are reduced due to the change in the composition of graphene.
[0150] In Comparative Examples 4-6, the stability and stain resistance of the obtained composite emulsion decreased due to the change in the composition of aminopolyethylene glycol.
[0151] In Comparative Examples 7-8, due to the composition of graphene-loaded nanosilver, the antibacterial property, antistatic property and wear resistance of the obtained composite emulsion decreased.
[0152] In Comparative Examples 9-11, due to the change in the composition of the core-shell polyurethane-acrylate composite emulsion, the flexibility and stain resistance of the obtained composite emulsion decreased.
[0153] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made by the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.
Claims
1. A nanosilver / graphene / polymer composite emulsion, characterized in that: The raw material composition is as follows: 2-8 parts of graphene-loaded nanosilver and 80-100 parts of polymer emulsion, wherein the polymer emulsion is a polyurethane-acrylate polymer emulsion having a core-shell structure; The method for preparing graphene comprises the following steps: S1, adding graphene to deionized water for ultrasonic mixing to obtain a graphene aqueous solution; S2, adding aminopolyethylene glycol to the graphene aqueous solution, reacting at 80-90° C. for 18-24 hours, filtering, washing with ethanol, and drying to obtain; The graphene is a compound of graphene oxide, porous graphene and nitrogen-doped graphene; the mass ratio is (10-20): (3-5): (0.5-1); The graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm; The pore size of the porous graphene is 3-5 nm; The nitrogen-doped graphene has a nitrogen content of 1-2 at% and a diameter of 0.5-10 μm; The amino polyethylene glycol is a compound of four-arm polyethylene glycol amino group and amino polyethylene glycol carboxyl group, with a mass ratio of (1-3): 1; The method for preparing the polyurethane-acrylate polymer emulsion with a core-shell structure comprises the following steps: S1. Preparation of polyurethane emulsion: under nitrogen protection, react pretreated castor oil, isocyanate and dibutyltin dilaurate at 70-90°C for 30-60min, add polyol and chain extender, and keep warm for 30-60min; cool to 60°C, add triethylamine for neutralization for 30-45min; cool to 20°C, add deionized water, and stir at 1000-3000r / min for 30-60min to obtain; S2. Preparation of core layer polyurethane grafted acrylic polymer: stir the first acrylate monomer, emulsifier, deionized water and polyurethane emulsion evenly, add ammonium persulfate at 60-70° C., and keep warm for 30-60 minutes to obtain; S3. Preparation of core-shell polyurethane-acrylate composite emulsion: Slowly add the second acrylate monomer and ammonium persulfate to the core layer polyurethane grafted acrylic polymer, react at 70-80° C. for 1-2 hours, and after the reaction is completed, add ammonia water dropwise to adjust the pH to 7-8 to obtain the product; The graphene-loaded nanosilver comprises a first graphene-loaded nanosilver and a second graphene-loaded nanosilver; the mass ratio of the first graphene-loaded nanosilver to the second graphene-loaded nanosilver is (20-30): (0.5-1.5); The preparation method of the first graphene-loaded nanosilver is as follows: first, 0.15 g of graphene is dispersed in 100 mL of deionized water and ultrasonicated for 1-2 h, then 25 mL of 50 mmol / L silver nitrate solution is added, and ultrasonicated for 20-30 min at 30-40° C.; then 0.02 g of NaBH4 is added, reacted at 25-30° C. for 10-12 h, 0.5 mol / L of sodium hydroxide aqueous solution is added during the reaction to adjust the pH of the system to 11, and finally, centrifuged after the reaction is completed, repeatedly washed with deionized water and ethanol, and dried to obtain the obtained product; The preparation method of the second graphene-loaded nanosilver is as follows: first, 0.15g of graphene is dispersed in 100mL of deionized water and ultrasonically treated for 1-2h, then 25mL of 50mmol / L silver nitrate solution is added, and ultrasonic treatment is performed at 30-40°C for 20-30min; then, 0.4g of sodium citrate and 3g of PVP are added, and after mixing evenly, 30mL of 20% hydrogen peroxide is added, and after stirring for 1-3min, 0.2g of NaBH4 is added, and after reacting for 40-60min, filtering, washing, and drying are performed to obtain the obtained product; The first acrylate monomer is a compound of butyl acrylate, hydroxyethyl acrylate and hydroxypropyl acrylate in a mass ratio of 1:(1-3):(2-4); The second acrylate monomer is a compound of methyl methacrylate, acrylic acid and ethyl acrylate in a mass ratio of (0.5-2):(4-6):(3-5); The polyol is a compound of polyethylene adipate and polybutylene adipate-1,4-diol, with a mass ratio of (1-3):
1.
2. A method for preparing the nanosilver / graphene / polymer composite emulsion according to claim 1, characterized in that: The following steps are involved: The graphene-loaded nanosilver and the polymer emulsion are ultrasonically mixed for 20-40 minutes to obtain the product.
3. An application of the nanosilver / graphene / polymer composite emulsion according to claim 1, characterized in that: Used as protective film coating for folding screens of electronic devices.
4. An application of the nanosilver / graphene / polymer composite emulsion prepared by the preparation method according to claim 2, characterized in that: Used as protective film coating for folding screens of electronic devices.
Citation Information
Patent Citations
Photocuring PET coating and preparation method thereof, and preparation method and application of PET base material
CN114163858A
Bending-resistant coating and bending-resistant film
CN115873461A
Functional graphene oxide loaded nano-silver antibacterial material as well as preparation method and application thereof
CN104472538A
Nano-silver loaded graphene antibacterial agent and graphene in-situ reduction nano-silver loaded water-based antibacterial coating
CN107815193A
Graphene and nano-silver composite material and preparation method thereof
CN113563759A